Pengaruh Brand Ambassador Brand Image dan Brand Identity Terhadap Keputusan Pembelian Scarlett Whitening Pada Tiktok Marketplace di Kota Batam - Christi, Aisya; Lutfhi, Andi Mulyadi; Raymond, Raymond (Universitas Batam, 2024)
Abstract - The objective of this study is to evaluate the influence of Brand Ambassador, Brand Image, and Brand Identity on Purchasing Decisions for Scarlett Whitening in the Tiktok Marketplace within Batam City. Scarlett Whitening experienced an increase in sales from 2019 to 2020, but then a significant decline from 2022 to 2023. This decline is believed to be related to a boycott that had a negative impact on consumer reputation and trust. Although the product packaging is attractive, the company's logo is considered too simple and does not adequately represent the diversity of its products, resulting in a misalignment of the brand's visual identity. Additionally, the selected brand ambassador has not been effective in mitigating the boycott issue, as evidenced by the continued decline in sales until the end of 2023. This research aims to investigate these factors and their impact on consumer purchasing decisions. A quantitative method is used in this study, with a population that includes residents of Batam City who have used Scarlett Whitening, and a sample of 96 respondents. The data analysis shows that the Brand Ambassador variable (X1) has a positive and significant partial effect on Purchasing Decisions, the Brand Image variable (X2) has a positive but insignificant effect on Purchasing Decisions, and the Brand Identity variable (X3) has a positive and significant partial effect on Purchasing Decisions. Additionally, there is a significant simultaneous effect of the Brand Ambassador, Brand Image, and Brand Identity variables on Purchasing Decisions for Scarlett Whitening in the Tiktok Marketplace in Batam City.